Improvement of an atypical Kikuchi-Fujimoto disease (KFD) with antidepressant treatment: the first psychiatric approach to a KFD case - Ozen, Murat Eren; Orum, Mehmet Hamdi; Kalenderoglu, Aysun; Atmaca, Murad (Taylor & Francis Ltd, 2019)
Kikuchi-Fujimoto disease (KFD) is a sporadic and benign disorder of the lymph nodes of young individuals. A preceding fever, occasional skin rashes, and lymphopenia, suggest a viral aetiology and there have been reports of viral association. However, so far, no infectious agent has been proved to be aetiologically related. We herein report KFD in a 27-year-old female who presented with fevers, weight loss and tender cervical lymph nodes. The patient had depressive symptoms before the onset of KFD. During the disease process, depressive symptoms worsened with the KFD course. She had not relieved with the supportive treatment and major depressive disorder (MDD) became more severe gradually. After the treatment of MDD and with the improvement of mental health, clinical symptoms and the lymph node growth became reversed. The authors conclude that this clinical course of KFD with the treatment of MDD suggests an immune system response or immunological problem in these patients.
Keywords: Kikuchi-Fujimoto disease; histiocytic necrotizing lymphadenitis; major depressive disorder; antidepressive agents